Perancangan Sistem Keamanan Lingkungan Berbasis Short Message Service Menggunakan Platform Arduino - Huda, Andi M. Nurul; Fajar, Mohammad; Munir, Abdul (STMIK KHARISMA Makassar, 2024)
This study aims to create an Short Message Service (SMS) based security system using the Arduino platform, where the system can be applied to every corner of the village in Indonesia. The system functions to play the sound of the danger signal whether it is theft or fire. The method used to remotely or or control the system is to use the Short Message Service (SMS) Tracking method, namely by sending an SMS command to play the sound of an alarm (Mp3). The system can run well such as receiving sms and processing the contents of the sms to play mp3 files, although there is still a little delay in receiving sms and playing the mp3.